'Maternal Flapping': Motherhood and National Sentiment in Elizabeth von Arnim's Letters to Beatrix von Hirschberg. Issue 2 (3rd April 2021) - Römhild, Juliane
ABSTRACT: To Elizabeth von Arnim, her experience of motherhood was associated with a particularly German coupling of sentimentality and brutality. This article explores the nexus between sentimentality, motherhood, German ideology, and the concept of Kultur in von Arnim's letters to her daughter Beatrix von Hirschberg. Spanning close to forty years, this correspondence, read in conjunction with von Arnim's short sketch 'Christmas in a Bavarian Village' (1937), offers a deeper understanding of von Arnim's political views and her experience of the vagaries of motherhood.